The status of Rhodesia in international law - Devine, Dermott J (Department of Public Law, 2018)
This thesis deals with the international law position of those entities which may be said to have status in relation to the territory known as Rhodesia (or Southern Rhodesia, if one is to give it its original name). These entities are the State of Rhodesia, the Government of Rhodesia, the People of Rhodesia and the United Kingdom which claims to exercise sovereignty over the territory of Rhodesia. Since the ambit of the thesis concerns the international law position of these entities it follows that other international law problems relating to Rhodesia, which concern third states and international organizations, fall outside its scope. These latter problems relate to obligations of third states and competences of international organizations to take action in the Rhodesian situation and do not relate to the status of Rhodesia itself. This thesis therefore does not deal with such matters as the imposition of sanctions by the United Nations and the obligations o f member states to participate in them. However, where obligations of third states are inextricably connected with the status of the territory itself, it is necessary to treat them. Thus the "duty not to recognize" Rhodesia owed by third states received full treatment in all its various facets for recognition is a concept which is of cardinal importance in considering status. For the purposes of exposition the thesis is divided into two main parts, a historical part and a contemporary part.